Port site hernia at the robotic arm port after robotic‐assisted laparoscopic radical prostatectomy - Ogasa, Taiki (IJU Case Rep, 2020)
INTRODUCTION: Complications unique to laparoscopic surgery have been reported, including port site hernia. We experienced a case of port site hernia in the robotic right‐hand port site measuring 8 mm in diameter after robotic‐assisted laparoscopic radical prostatectomy. CASE PRESENTATION: A 56‐year‐old man was indicated a high prostate–specific antigen level of 37.8 ng/ml. Subsequent prostate biopsy revealed adenocarcinoma with a Gleason score of 4 + 4. The patient underwent robotic‐assisted laparoscopic radical prostatectomy in Juntendo Hospital. Although his postoperative recovery was generally good, the patient complained of sudden nausea and acute abdominal pain. A contrast computed tomography scan showed an ileus due to a hernia occurring at the robotic right‐hand port, the da Vinci Arm I port. We released incarceration under laparoscopic procedure. CONCLUSION: Since the port diameter is relatively small in robot‐assisted surgery, port site hernias are expected to be rare. However, careful attention should be paid to the positional deviation of the remote center.